PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP NEGERI 14 PEKANBARU - Muliana Maria Br Tarihoran; Atma Murni; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The background of this research is the low ability of students' problem solving of mathematics which causes the low result of the mathematics students learning. This research is a pre-experimental research and use the design of The Static Group Comparison. Population in this research is all grade VIII students in SMP Negeri 14 Pekanbaru. The sample in this research consists of two class, where the VIII4 as a control class and the VIII7 as as experimental class. The purpose of this research is to know the effect of implemantation problem solving strategy in think pair share (tps) structural approach of cooperative learning towards students mathematics problem solving ability in KD 3.1 generalizing of patterns on sequence numbers and sequences of object configuration and KD 4.1 resolving problems related to patterns sequence of numbers and sequences of object configuration. The instruments in this research were mathematical early ability test and mathematical problem ability test (postest). The result of mathematical early ability test was used for determining the sample of class. The postest result was analyzed by nonparametric statistic test of Mann Whitney. The result of the research showed that implementation problem solving strategy in think pair share (tps) structural approach of cooperative learning give the positive effect towards students mathematical problem solving ability at class VIII SMP Negeri 14 Pekanbaru. The implementation of problem solving strategy in think pair share (tps) structural approach of cooperative learning gave effect for 31,30% towards students mathematical problem solving ability at class VIII SMP Negeri 14 Pekanbaru and included in the minimum category.Key Words: Problem solving strategies, Think Pair Share structural approach to Cooperative learning, Mathematical Problem Solving Ability